Feedback on adding game elements and quizzes in engineering theoretical subjects/ Mohammad Abdullah and Soo Kum Yoke - Abdullah, Mohammad; Soo, Kum Yoke (UiTM Cawangan Johor, 2024)
Engineering subjects that are heavily theoretical may cause students to get bored and lose interest in engineering studies. It will not only make students fall asleep but also prevent them from comprehending the specifics of the subject matter. In view of this, several ways can be used to ensure the learning atmosphere is more effective and less boring, such as quizzes, games, and interactive learning. Therefore, this paper intends to give feedback regarding adding games and quizzes in theoretical subjects. Adding games and quizzes in the classroom makes learning activities more cheerful, and students are always eager to focus on learning. Among the games that can apply are puzzle games, Kahoot, and Jenga. Adding games makes students more competitive in answering the questions asked in class and, simultaneously, makes them quickly understand the theory learned in class. This paper describes students' responses to using games and quizzes in theoretical subjects in class. To get feedback, surveys with game and quiz components were used to gauge student happiness and the quality of instruction in the classroom. Students gain from adding game and quiz components to theoretical subjects in few ways: they learn more quickly, do not feel sleepy, and the classroom is more upbeat and understandable.